2016
DOI: 10.3847/2041-8205/816/2/l30
|View full text |Cite
|
Sign up to set email alerts
|

Neutron-Star Merger Ejecta as Obstacles to Neutrino-Powered Jets of Gamma-Ray Bursts

Abstract: We present the first special relativistic, axisymmetric hydrodynamic simulations of black hole-torus systems (approximating general relativistic gravity) as remnants of binary-neutron star (NS-NS) and neutron star-black hole (NS-BH) mergers, in which the viscously driven evolution of the accretion torus is followed with selfconsistent energy-dependent neutrino transport and the interaction with the cloud of dynamical ejecta expelled during the NS-NS merging is taken into account. The modeled torus masses, BH m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
167
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(177 citation statements)
references
References 48 publications
6
167
4
Order By: Relevance
“…This is because even a tiny mass of baryons polluting the jet will severely limit the maximum attainable Lorentz factor and effective jet triggering might have to wait until after black hole collapse. In scenario a, the wind emanating from the HMNS hampers the advancement of a relativistic jet, leading to a low luminosity event (Rosswog & RamirezRuiz 2002, 2003Nagakura et al 2014;Just et al 2016). In scenario b in Figure 1, the collapse to a black hole occurs (green) and L * = 0.7 × 10 51 erg/s, a = 0.6 promptly and a classical jetted sGRB is produced which we happen to view off-axis (such as Ramirez-Ruiz et al 2005).…”
Section: Metabolics Of Gw170817/sss17amentioning
confidence: 99%
“…This is because even a tiny mass of baryons polluting the jet will severely limit the maximum attainable Lorentz factor and effective jet triggering might have to wait until after black hole collapse. In scenario a, the wind emanating from the HMNS hampers the advancement of a relativistic jet, leading to a low luminosity event (Rosswog & RamirezRuiz 2002, 2003Nagakura et al 2014;Just et al 2016). In scenario b in Figure 1, the collapse to a black hole occurs (green) and L * = 0.7 × 10 51 erg/s, a = 0.6 promptly and a classical jetted sGRB is produced which we happen to view off-axis (such as Ramirez-Ruiz et al 2005).…”
Section: Metabolics Of Gw170817/sss17amentioning
confidence: 99%
“…As it is found that neutrinos might play an important role only at the highest mass accretion rates (e.g. Janiuk et al 2007, Janiuk et al 2013, Just et al 2016), we will not consider this mechanism here. Instead, we will focus on scenarios where the rotational energy of a spinning BH is extracted by a large scale magnetic field threading the disk (Blandford & Znajek 1977).…”
Section: Viscous Evolution Of Self-gravitating Clumpsmentioning
confidence: 99%
“…In [12], we addressed the question if νν-annihilation in post-merger BH-torus systems is efficient enough for the resulting jet-like outflow to penetrate the cloud of dynamical ejecta and to explain sGRBs. Likewise to [8] we employed the ALCAR-AENUS code [13] but upgraded its Newtonian hydrodynamics module to a special relativistic version.…”
Section: Grb Relevant Outflow Componentmentioning
confidence: 99%
“…Color maps of density, ρ, energy deposition rate by νν-annihilation, Q ann , proton-to-baryon ratio, Y e , Lorentz factor, Γ, and terminal Lorentz factor, Γ times specific enthalpy density h, for a choked annihilationdriven jet at 300 ms after a 1.2 − 1.8 M ⊙ NS-NS merger, shortly before dissipating its remaining kinetic energy in the surrounding envelope of dynamical ejecta. Figure adopted from [12].…”
Section: Grb Relevant Outflow Componentmentioning
confidence: 99%